Pengaruh Kualitas Layanan dan Keadilan Terhadap Kepatuhan Wajib Pajak Dengan Kepuasan Sebagai Variabel Mediasi - Eka Febriani; Norra Isnasia Rahayu (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2020)
This study aims to examine the effect of service quality and fairness on taxpayer compliance and the mediating role of satisfaction in the effect of service quality and fairness on taxpayer compliance. The population of this research is individual local taxpayers in Samarinda. The sample of this study is 164 respondents selected using non probability method with convenience sampling technique. This study uses primary data obtained from seven-scale Likert questionnaires. The data were analyzed using path analysis in SPSS. The results of this study show that, first, service quality has a significant positive effect on satisfaction and taxpayer compliance; second, fairness has an insignificant effect on satisfaction and taxpayer compliance; third, satisfaction has a significant positive effect on taxpayer compliance; fourth, service quality has a significant positive effect on taxpayer compliance mediated by satisfaction; fifth, mediated by satisfaction, fairness has no significant effect on tax compliance.